PEMBERITAAN KASUS PINJAMAN ONLINE ILEGAL DI MEDIA BERITA ELEKTRONIK - ARIGATO DIMITRI BATISTUTA,; CHONTINA SIAHAAN, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
There are a lot of an illegal online loan institution or peer to peer financial technology lately that causing a worry. Many cutomers harmed because they had borrowed from that online loan institution. Some of the causes are the debt collector’s behavior from the online loan institution that threatened the customers with a pornography content if they don’t pay their instalment. Then, a threat about the spread of the customer’s personal identity. Also, the threat about increasing the interest on the loan more than the previous agreement. As a result, the online loan institution customers feel depressed and they finally decided to suicide because they cannot afford the instalment and the interest. This problem is considered very worrying and need to be handled effectively to eradicate the illegal online loan and freed the victims of that illegal online loan.